2020
DOI: 10.1038/s41375-020-0771-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the role of the innate immune response in relapse or blast crisis in chronic myeloid leukemia

Abstract: Chronic myeloid leukemia (CML) is characterized by expression of the tyrosine kinase oncogene, Bcr-abl. Tyrosine kinase inhibitors (TKI) induce prolonged remission in CML, and therapy discontinuation is an accepted approach to patients with reduction in Bcr-abl transcripts of four logs or greater. Half such individuals sustain a therapy free remission, but molecular mechanisms predicting relapse are undefined. We found relative calpain inhibition in CML cells with stabilization of calpain substrates, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…At present, none of the TKIs seems to be able to achieve this result, neither through a direct drug action nor through a time-dependent mechanism sustained by continuous drug pressure and/or immune surveillance effects leading to a progressive exhaustion of Ph+ LSC. Immunologic mechanisms are often invoked but, at present, they remain hypothetical [ 59 , 60 , 61 ]. Some evidence on a specific role of lymphocyte sub populations (NK) has been reported, but deeper studies of the immunologic mechanisms in CML patients during TKI treatment should be addressed [ 62 , 63 ].…”
mentioning
confidence: 99%
“…At present, none of the TKIs seems to be able to achieve this result, neither through a direct drug action nor through a time-dependent mechanism sustained by continuous drug pressure and/or immune surveillance effects leading to a progressive exhaustion of Ph+ LSC. Immunologic mechanisms are often invoked but, at present, they remain hypothetical [ 59 , 60 , 61 ]. Some evidence on a specific role of lymphocyte sub populations (NK) has been reported, but deeper studies of the immunologic mechanisms in CML patients during TKI treatment should be addressed [ 62 , 63 ].…”
mentioning
confidence: 99%
“…Furthermore, we demonstrated increased sensitivity of p190 cells to two classes of apoptotic modulators, IAP inhibitors, and P53 modulators/MDM2 antagonists. IAP inhibitors/ SMAC mimetic drugs (ex: LCL161) target the antiapoptotic IAP molecules including cIAP1, cIAP2, and survivin and have shown potential activity in CML as a monotherapy and in combination with TKI [47][48][49]. Interestingly, p190 has been shown to cooperate with Src activation to drive γcatenin/MYC-induced survivin overexpression [50], which may partly explain enhanced sensitivity of p190 cells to IAP inhibitors over p210.…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding that some putative LSCs lack leukemogenic potential [13] and that individuals who have BCR-ABL1 transcripts detectable at low levels in their peripheral blood (PB) but are otherwise healthy were observed in some old studies [14,15], suggest that there is heterogeneity in LSCs and that the generation of LSCs from HSCs and their ability to function as leukemia initiating cells (LICs) are the result of an interplay between cell-intrinsic and cell-extrinsic factors. For example, an RNA-seq analysis found that gene expression profiles associated with activated immune response were downregulated in BCR-ABL1-positive HSCs from mice that developed leukemia as compared to those from mice that did not [16]-pointing to a role for the immune response in regulating the leukemogenic potential of BCR-ABL1-positive LSCs.…”
Section: Figurementioning
confidence: 99%